'It is our duty:' understanding parents' perspectives on reproductive and sexual health education. Issue 5 (2nd September 2020) - Cameron, Amanda; Smith, Ellie; Mercer, Nicholas; Sundstrom, Beth
ABSTRACT: South Carolina ranks 16 th in the USA for highest rates of teenage pregnancy. The South Carolina Comprehensive Health Education Act (CHEA) does not require medically accurate, unbiased, culturally appropriate materials, and varies greatly in compliance and implementation. This study aimed to better understand parents' perspectives in one county in South Carolina regarding reproductive and sexual health education. A total of 484 parents responded to a qualitative questionnaire, collectively representing 798 students. Researchers conducted a thematic analysis to organise the data. Main themes identified include comprehensive reproductive and sexual health education as a duty; dispelling the myth of abstinence-only education; and the value of comprehensive reproductive and sexual health education. Parents described teaching reproductive sexual health education in public schools as a 'duty.' Furthermore, parents rejected the idea that abstinence-only education is effective and believed reproductive and sexual health education should be taught without the influence of religion. Parents valued inclusive reproductive and sexual health education, covering a robust set of topics. Findings from the study provide evidence for the need to update current reproductive and sexual health education materials and legislation to meet parental demands and reduce youth sexual and reproductive health disparities.